Iron-Catalyzed Carboiodination of Alkynes - Deng, Weili; Li, Yajun; Li, You-Gui; Bao, Hongli (Synthesis, 2018)
An iron-catalyzed carboiodination of alkynes with alkyl iodides at room temperature was developed. This method could provide synthetically useful vinyl iodides with general alkyl chains, fluoroalkyl group, ester, and cyano group. Conjugated alkynes or unconjugated alkynes were both suitable for this transformation. A radical pathway was proposed for the mechanism and acetyl tert-butyl peroxide was selected as the radical initiator. Alkenes could also be applied to this chemistry and produce more complex alkyl iodides.
Keywords: iron catalysis; radical; alkyl iodides; alkynes; carboiodination